GEOGRAPHIC INFORMATION SYSTEMS FOR AGRICULTURAL SUITABLE LAND AT KABUPATEN SLEMAN - Agus Qomaruddin Munir; Indra Listiawan; Evrita Lusiana Utari; Muh. Ridho Wahid Solihin (Jurnal Teknik Informatika (Jutif), 2023)
Indonesia is an agricultural country, the growth rate of various food and crops tends to be stable. However, some plants in certain areas are different from what is expected. This study aims to investigate land suitability for crops such as rice, analysis of development potential, and develop recommendations for land use for agricultural types, Sleman Regency, Special Region of Yogyakarta. Landsat 8 imagery is used for land use extraction as input for making land use directions for agricultural and forestry plant species. The method used in this study is a combination of analysis of Landsat 8 imagery and field data processed using a Geographic Information System in making thematic maps of the physical characteristics of the land to obtain land suitability maps for agricultural crop species and with a weighting method in stages based on the physical parameters of the conditions for growing crops. The analysis results are used to formulate land use directions for the types of crops in Sleman Regency. An area very ideal for the type of rice plant and land planted. For crops, it is directed based on the room's function, namely in the cultivation area. Sites that have the potential to be developed for crops are produced and set in buffer zones because more emphasis is placed on conservation aspects and increasing crop productivity. This geographic information system is one of the recommendations to be used as a reference by farmers in increasing the productivity of agricultural land.